2020
DOI: 10.1038/s42003-020-0856-x
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem-wide metagenomic binning enables prediction of ecological niches from genomes

Abstract: The genome encodes the metabolic and functional capabilities of an organism and should be a major determinant of its ecological niche. Yet, it is unknown if the niche can be predicted directly from the genome. Here, we conduct metagenomic binning on 123 water samples spanning major environmental gradients of the Baltic Sea. The resulting 1961 metagenomeassembled genomes represent 352 species-level clusters that correspond to 1/3 of the metagenome sequences of the prokaryotic size-fraction. By using machine-lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(102 citation statements)
references
References 77 publications
2
100
0
Order By: Relevance
“…in any Baltic Sea water sample. In support of this, eleven metagenomeassembled genomes (MAGs) of Nitrospinae were extracted from the Baltic Sea metagenomes (Alneberg et al, 2020), and none of these contained hgcAB-like genes (data not shown). Microbial syntrophy, defined as an obligate mutualistic metabolism, is a process known to occur mainly in environments with shortage of favorable electron acceptors, e.g., mostly in anoxic environments (McInerney et al, 2009;Morris et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…in any Baltic Sea water sample. In support of this, eleven metagenomeassembled genomes (MAGs) of Nitrospinae were extracted from the Baltic Sea metagenomes (Alneberg et al, 2020), and none of these contained hgcAB-like genes (data not shown). Microbial syntrophy, defined as an obligate mutualistic metabolism, is a process known to occur mainly in environments with shortage of favorable electron acceptors, e.g., mostly in anoxic environments (McInerney et al, 2009;Morris et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…in any Baltic Sea water sample. In support of this, eleven metagenome-assembled genomes (MAGs) of Nitrospinae were extracted from the Baltic Sea metagenomes ( Alneberg et al, 2020 ), and none of these contained hgcAB -like genes (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…Smith et al 2015 [87] demonstrated that microbial community composition as determined by 16S rRNA can be used to predict a diverse set of geochemical factors including pH, manganese and aluminum. Alneberg et al (2020) [97] also highlight the application of SML to predict the ecological niche of microbial groups with a focus on microbial communities from the Baltic Sea. The authors of this study use metagenomic binning to obtain 1962 metagenome assembled genomes (MAGs) representing the majority of prokaryotic diversity in in the Baltic Sea.…”
Section: Optimizing Model Construction and Evaluationmentioning
confidence: 99%
“…While this approach was here applied to the case of bloom-forming cyanobacteria, there is in principle no reason why this approach may not find application in a variety of other microbial habitats and organismal groups. On a broader scale, our approach can be combined with metagenome-assembled genomes to infer the link between genomic complexity and ecological niche, where together they could provide a comprehensive conceptual framework for predictive ecology from genomic data (52).…”
Section: Figmentioning
confidence: 99%